Built-in social : essential social marketing practices for every small business - Korhan, Jeff, 1957- (Wiley, 2013)
How to redesign your business for social relevance and profitable success Marketing today is driven by the customer. The old mindset was finding customers for your products and services. The new one is collaborating with the customers whose trust you have earned to develop better products and services for them. Businesses that succeed today acknowledge that they are in shared relationships with customers, employees, and other influencers in the community-even competitors. Built-In Social provides a step-by-step approach to building a business channel that aligns your business w.